ANALISIS HUBUNGAN MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA BISNIS : STUDI KASUS BENGEKEL TRUK ADI AMIR DI KOTA BINJAI - Bunayyati Hakimah S. Meliala; Diah Safri Yulinda; Siti Aisyah (Transpublika Publisher, 2022)
Adi Amir Truck Workshop is an automotive repair shop that offers goods and services by engaging in repairing all damage that occurs to truck cars, whether damage to the engine, to the head of the car, to the tailgate or anything related to other truck cars. This research method uses a descriptive approach that describes phenomena that occur in the present or in the past with data collection techniques, namely direct interviews with business owners and interviewing people who are really involved in the problems of this research, as well as taking various information. from the internet with credible sources. The results of this study show that Ho is rejected and Ha is accepted, which means that there is a significant relationship between Supply Chain Management and business performance at the Adi Amir Truck Workshop.